Spatio-Temporal Regulation of IGFs in Enamel Development: Molecular Mechanisms From Ameloblast Polarity to Mineralization Homeostasis - Xue Zeng; Pengcheng He (Stem Cells International)
The development of enamel relies on the precise regulation of ameloblast differentiation, enamel matrix secretion, and mineralization. The formation of enamel is crucial for the normal function of dental tissues, and promoting enamel remineralization is of significant importance for the treatment of dental caries. Understanding the underlying mechanisms of enamel development is essential for oral therapy and provides a bridge to tooth regeneration. Among various growth factors, the insulin-like growth factor (IGF) family, including IGF-1 and IGF-2, has been shown to play a key role in enamel formation by activating signaling pathways such as PI3K/AKT and MAPK. This review summarizes the role of the IGF family in tooth development and enamel formation and sheds light on key parts of the research for future treatment improvements.